SERUM CONCENTRATION OF INTERLEUKIN - Al-Dabagh, Muhammed; Al-Mayah, Kasim; Muhammed, Ghaneima; Alkhafaji, Jassem; Jawad, Ali; Abbas, Mohammed (Iraqi Journal of Science, 2024)
Interleukin-1( IL-1) and interleukin 8 (IL-8) have a major role in initiation ofimmune response. These two cytokines are secreted mainly by monocyte. This studyaimed to evaluate the initiation of immune response in patients with acutelymphoblastic leukemia. Blood samples were collected from 36 patients with ALL(26 treated and 10 untreated ). Other 10 blood samples were collected from healthyindividuals as control group. Enzyme linked immunosorbent assay (ELISA) wasused to estimate serum concentration of IL-1 and IL-8. Absolute monocyte count ineach blood sample was determined. The study showed a significant decrease inserum concentration of IL-1 in treated and untreated patients, whereas, serumconcentration of IL-8 and blood absolute monocyte count showed significantincrease in untreated patients. Dropping in IL-1 and elevation of IL-8 withincreasing absolute monocyte count may indicate suppression of gene expression forIL-1 but not for IL-8.